Return to Sport Following ACL Reconstruction With Slope-Correcting High Tibial Osteotomy in the Elite Athlete - Walter R. Lowe MD; Alfred Mansour MD; Steven Higbie PT, DPT, SCS, CSCS; Connor Galloway PT, DPT, MS, SCS, LAT; Jacquelyn Kleihege PT, MPT, SCS; Lane Bailey PT, PhD (SAGE Publishing, 2023)
Background: Increased posterior tibial slope is a strong predictor of anterior cruciate ligament (ACL) graft re-injury. A concomitant slope-reducing high tibial osteotomy (HTO) has been suggested to decrease re-tear risk in these cases although little is known regarding outcomes following ACL reconstruction with HTO, especially in elite athletic patients. Indications: A 19-year-old National Collegiate Athletics Association (NCAA) Division 1 running back presented with an ACL tear, lateral meniscus tear, and posterior tibial slope of 19° (case 1). A 19-year-old NCAA Division 1 soccer forward presented with an ACL graft re-tear and posterior tibial slope of 21° (case 2). Technique: Anterior closing wedge HTOs were performed along with a primary ACL reconstruction with quadriceps tendon autograft (case 1) and a revision ACL reconstruction with quadriceps tendon autograft (case 2). Following the arthroscopic procedures, an anterior approach was used to insert the first guide wire distal to the patellar tendon insertion from anterior to posterior aiming toward the posterior curve of the tibia. A second guide wire was placed at the previously templated distance. The osteotomy was then performed utilizing a saw and then osteotome. The reduction was performed by gently lifting the ankle anteriorly and applying axial pressure, and a new posterior tibial slope was calculated. After the osteotomy site was reduced, a preliminary reduction was performed by applying a clamp to both wires followed by placing a wire across the osteotomy site aiming from anterolateral to posteromedial. An anterolateral proximal tibial plate was applied, as well as a lag screw across the osteotomy site. Results: At 6 months after surgery, case 1 demonstrated >90% Limb Symmetry Indices (LSI) with quadriceps strength, single leg hop tests, and change of direction tests. At 12 months after surgery, case 2 demonstrated >90% LSI with all functional testing and competed in 17 games. Both patients returned to preinjury performance metrics including top speed and vertical jump height. No significant postoperative complications or instability was observed. Discussion/Conclusion: Primary or revision ACL reconstruction with HTO shows potential to assist athletes in returning to high-level sport while reducing posterior slope. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.